Remdesivir triphosphate as a potential repurposed drug against the emerging Bundibugyo Ebolavirus 2026 - Mansi Dutt; Misaki Wayengera; Gustavo Sganzerla Martinez; Anuj Kumar; Andrew Nsawotebba; Isaac Ssewanya; Suzan Nabadda; Barnabas Bakamutumaho; Bruce Kirenga; Charles Olaro; Winters Muttamba; Pauline Byakika; et al. (Journal of Infection, 2026)
Bundibugyo virus disease (BVD) is a rare and often fatal form of Ebola disease caused by the contagious Bundibugyo virus (BDBV), a member of the Orthoebolavirus (formerly Ebolavirus) genus within the family Filoviridae family.1 This zoonotic disease is a deadly illness with a reported morality rate range from 30 to 50%.2 Currently, two East-central African countries, namely, the Democratic Republic of Congo (DRC) and Uganda have had outbreaks of the rare BDBV. On 17 May 2026, World Health Organization (WHO) declared multiple Ebola outbreaks as a Public Health Emergency of International Concern (PHEIC) due to a surge in the number of confirmed deaths and cases. As of 23 May 2026, a total of the 83 confirmed cases, 9 confirmed deaths with 746 suspected cases and 176 suspected deaths, have been reported from the Ituri, Nord-Kivu, South-Kivu provinces of DRC with a Case Fatality Rate (CFR) of 11%. Uganda has reported 5 confirmed cases and 1 confirmed death.3 These confirmed cases reported from Uganda are linked to the people who have recent history of travel from the DRC or contact with confirmed travel cases of BDBV.
Canadian Institutes of Health Research, Mpox Rapid Research Funding Initiative (CIHR MZ1 187236,) , Moderna Global Fellowship 2024 (2024-MGF- 000316 [91353], the Li Ka Shing Foundation and Ministry of Health, Uganda.
Keywords: Bundibugyo virus disease (BVD); Ebola disease; World Health Organization (WHO)